Demonstration field experiment on testing nematode-resistant potato varieties in the Vladimir Region - A. A. Shesteperov; M. A. Morozov (Российский паразитологический журнал, 2021)
The purpose of the research is a demonstration field experiment on testing nematode-resistant potato varieties on a collective farm in focal point of golden potato nematode (GPN).Materials and methods. A demonstration field experiment on testing 7 nematode-resistant and 2 susceptible potato varieties was performed in the village of Parakhino, Gus-Khrustalny District, Vladimir Region, in a small family garden with significant evidences of potato globoderosis. The family garden was divided into 27 plots. The plot area was 100 m2 . In spring and autumn, 500 cm3 soil samples were taken from each plot. The soil samples were studied by the flotation funnel method. In growing season, we measured the height of plants, counted the number of stems, estimated the color, considered the uniformity and projected coverage of grass stand of the soil, assessed the globoderosis development, and determined the number of female GPN and their development on plant roots. During the harvesting period, we took into account the number and weight of potato tubers (standard and nonstandard) in 25 plants on each plot and the number of plants on the plot, and determined potato yields. We calculated the biological and economic effectiveness of growing nematode-resistant potato varieties.Results and discussion. The demonstration field experiments of 7 nematode-resistant potato varieties using modern mechanized potato cultivation techniques in the globoderosis focus faced by high infective rate (pre-plant density of the GPN population was 9.7–10 thousand eggs and larvae per 100 cm3 of soil) showed that the nematode-resistant varieties of Saturna, Lady Rosetta, Lady Claire, Malinovka, Latonna, Skarb, Zhukovsky Ranny surpassed susceptible cultivar Udacha (standard) in biological effectiveness (57–85%), economic effectiveness (4.9–134%) and economic benefit (87–409%). In susceptible cultivars Udacha and Germes, the globoderosis development was above 53%. In the tested nematode-resistant cultivars, the globoderosis development was poorly expressed (15–26%). Nematode-resistant cultivars Lady Claire, Lady Rosetta and Saturna, which showed the highest levels of profitability, economic efficiency, and high rates of decrease in the GPN population density in the soil can be recommended for cultivation in the fields of the Rossiya agricultural company. Susceptible cultivar Germes, which has shown good performance in terms of economic effectiveness and benefit can be recommended for cultivation in the crop rotation fields of the Rossiya agricultural company. Nematode-resistant cultivars Malinovka, Skarb, Latonna and Zhukovsky Ranny, which showed less economic effectiveness and benefit as compared to potato varieties for chips can be recommended for cultivation in private plots if cultivated using modern technology.